Group Collision Tracking Tree for Passive Multi-Tags RFID Systems - Yaacob, Marizan; Shafie, Noraimi; Mohamed, Norliza; Azizan, Azizul (International Journal of Integrated Engineering, 2024)
The Radio Frequency Identification (RFID) system is gaining widespread adoption, gradually replacing the traditional barcode system. Multi-tag RFID systems are commonly used and rely on passive RFID tags, which are battery-free and powered by electromagnetic waves emitted by the reader. These passive tags are cost-effective compared to active tags with batteries. However, a significant challenge in multi-tag RFID systems is tag collisions, where multiple tags respond simultaneously when the reader queries them. This paper proposes a novel group collision resolution technique of tree-based algorithm. The algorithm categorizes tags into two groups based on the Most Significant Bit (MSB) of their identification (ID). The first group comprises tags with an ID starting with 0X, while the second group consists of tags with an ID starting with 1X. The algorithm utilizes Manchester coding to track the collision bit strategically. This method of grouping is effective, as it rapidly separates tags into segmented groups, reducing the likelihood of tag collisions. The proposed algorithm group-collision tracking tree (GCTT) outperforms existing collision-tracking (CT), and bi-response collision tree (BCT) tree-based algorithms in terms of response time in reading all tags. In summary, the grouping and collision tracking offers promising advancements in the field of tag sorting and enhancing the overall efficiency of multi-tag RFID systems.